Miss Nelson is missing! - Allard, Harry; Marshall, James (New York : Houghton Mifflin Company, 1977)
The kids in room 207 take advantage of their teacher's good nature until she disappears and they are faced with a vile substitute.
K-3.
Keywords: School stories; Teacher -- Fiction